Essentials of genetics - Klug, William S.; Ward, Sarah M. (Pearson, 2013)
Known for its focus on conceptual understanding, problem solving, and practical explanations, this text strengthens problem solving coverage and explores the essential genetics content today's students need to know. This edition maintains the book's briefer, less-detailed approach to teaching core concepts. New features of the Eighth Edition include four new Special Topics chapters and thorough updates